Numerical analysis of non-constant pure rate of time preference: A model of climate policy - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2008)
When current decisions affect welfare in the far-distant future, as with climate change, the use of a declining pure rate of time preference (PRTP) provides potentially important modeling flexibility. The difficulty of analyzing models with non-constant PRTP limits their application. We describe and provide software (available online) to implement an algorithm to numerically obtain a Markov perfect equilibrium for an optimal control problem with non-constant PRTP. We apply this software to a simplified version of the numerical climate change model used in the Stern Review. For our calibration, the policy recommendations are less sensitive to the PRTP than widely believed. (C) 2008 Elsevier Inc. All rights reserved.